The Impact of Individualized Hemodynamic Management on Intraoperative Fluid Balance and Hemodynamic Interventions during Spine Surgery in the Prone Position: A Prospective Randomized Trial - Kukralova, Lucie; Dostalova, Vlasta; Cihlo, Miroslav; Kraus, Jaroslav; Dostal, Pavel (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: The effect of individualized hemodynamic management on the intraoperative use of fluids and other hemodynamic interventions in patients undergoing spinal surgery in the prone position is controversial. This study aimed to evaluate how the use of individualized hemodynamic management based on extended continuous non-invasive hemodynamic monitoring modifies intraoperative hemodynamic interventions compared to conventional hemodynamic monitoring with intermittent non-invasive blood pressure measurements. Methods: Fifty adult patients (American Society of Anesthesiologists physical status I−III) who underwent spinal procedures in the prone position and were then managed with a restrictive fluid strategy were prospectively randomized into intervention and control groups. In the intervention group, individualized hemodynamic management followed a goal-directed protocol based on continuously non-invasively measured blood pressure, heart rate, cardiac output, systemic vascular resistance, and stroke volume variation. In the control group, patients were monitored using intermittent non-invasive blood pressure monitoring, and the choice of hemodynamic intervention was left to the discretion of the attending anesthesiologist. Results: In the intervention group, more hypotensive episodes (3 (2−4) vs. 1 (0−2), p = 0.0001), higher intraoperative dose of ephedrine (0 (0−10) vs. 0 (0−0) mg, p = 0.0008), and more positive fluid balance (680 (510−937) vs. 270 (196−377) ml, p < 0.0001) were recorded. Intraoperative norepinephrine dose and postoperative outcomes did not differ between the groups. Conclusions: Individualized hemodynamic management based on data from extended non-invasive hemodynamic monitoring significantly modified intraoperative hemodynamic management and was associated with a higher number of hemodynamic interventions and a more positive fluid balance.
Keywords: Prone Position; stroke volume variation; Water-Electrolyte Balance; Adult; Prospective Studies; dospělí; stroke volume; goal-directed fluid therapy; Patient Positioning; Hemodynamics; pronační poloha; hemodynamic monitoring; spine surgery; lidé; Humans; polohování pacienta; hemodynamika; vodní a elektrolytová rovnováha; prospektivní studie